Regionalism under Challenge: Ideas and Joko Widodo’s Foreign Policy towards ASEAN, 2014-2019 - Mohamad Rosyidin; Shary Charlotte H. Pattipeilohy (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2020)
Indonesia’s foreign policy under Joko Widodo ‘Jokowi’ has significantly shifted compared with his predecessor’s era, especially regarding policies on regionalism. While former President Susilo Bambang Yudhoyono emphasises multilateralism with a particular focus on ASEAN, Jokowi’s administration tends to overlook ASEAN as a multilateral organization. The research investigates the causal root of the tendency by using the concept of ideas in foreign policy. The results argue that the diminished role of Indonesia in ASEAN, especially during the first term of Jokowi’s presidency, is strongly influenced by causal beliefs held by Indonesian political elites and presidential advisors. Despite varying from one individual to another, these ideas have similar characteristics in proposing that Indonesia should expand its concentric circle beyond ASEAN, arguing that ASEAN is intrinsically weak and thus can no longer accommodate Indonesian aspirations. This idea acts as a road map that defines Indonesia’s national interests amid international politics dynamics in the 21st century.